A sulfotransferase dosage-dependently regulates mouthpart polyphenism in the nematode Pristionchus pacificus. Issue 1 (December 2018) - Bui, Linh; Ivers, Nicholas; Ragsdale, Erik
Abstract Polyphenism, the extreme form of developmental plasticity, is the ability of a genotype to produce discrete morphologies matched to alternative environments. Because polyphenism is likely to be under switch-like molecular control, a comparative genetic approach could reveal the molecular targets of plasticity evolution. Here we report that the lineage-specific sulfotransferase SEUD-1, which responds to environmental cues, dosage-dependently regulates polyphenism of mouthparts in the nematodePristionchus pacificus . SEUD-1 is expressed in cells producing dimorphic morphologies, thereby integrating an intercellular signalling mechanism at its ultimate target. Additionally, multiple alterations ofseud-1 support it as a potential target for plasticity evolution. First, a recent duplication ofseud-1 in a sister species reveals a direct correlation between genomic dosage and polyphenism threshold. Second, inbreeding to produce divergent polyphenism thresholds resulted in changes in transcriptional dosage ofseud-1 . Our study thus offers a genetic explanation for how plastic responses evolve. Certain genotypes define developmental plasticity and discrete morphologies, but a mechanism as to how this arises is unclear. Here, the authors show that dosage-specific sulfotransferase (SEUD-1) expression specifies which mouthparts are expressed in the nematodePristionchus pacificus, dependent on the environment.